Regulating Media Pluralism in Algerian Legislation - Belouadah, Tayeb (Journal of Legal Studies and Researches, 2017)
Freedom of opinion and expression is one of the corner stones of democracy; this is why it should never be monopolized by the mono-scale media organizations because this violates the right of citizens to multi-media on the grounds that it leads to guide public opinion and dominate it. For this reason, the various media laws tended to regulate pluralism in the media. For his part, the Algerian legislature has tried to embody all this in the Algerian Media law No.12-05.